Improving regional fertilizer markets in West Africa - Bumb, Balu L.; Johnson, Michael E.; Fuentes, Porfirio A. (International Food Policy Research Institute, 2012)
In 2000, the member states of the Economic Community of West African States (ECOWAS) signaled their commitment to the United Nations’ Millennium Development Goal of halving hunger and poverty by 2015 (MDG1). To achieve that goal, agriculture in the region needed to grow by 6.8 percent annually. From 2000 to 2009, however, West African agriculture grew at half the desired rate—3.7 percent—due to many biophysical and socioeconomic constraints, including heavy reliance on rainfed production systems, traditional practices of soil fertility maintenance, and limited access to markets. Consequently, crop yields in West Africa are significantly lower than global averages, and their rate of increase has barely kept up with population growth. Cereal production in West Africa increased by 4.4 percent per annum from 1980 to 2009, an annual growth rate only marginally above the population growth rate. About two-thirds of this growth was accounted for by expanding cultivated area; one-third represented yield growth.